القيادة التحويلية وأثرها على أداء الموارد البشرية دراسة ميدانية في مصرف شمال افريقيا - فرع صبراتة (Comprehensive Journal of Science, 2025)
This study aimed to determine the impact of transformational leadership, with its various dimensions, on human resource performance at the North Africa Bank – Sabratha Branch. The significance of the study lies in the urgent need to enhance the functional performance of human resources within a banking environment facing increasing challenges, including improving operational efficiency and the quality of banking services.The study relied on two primary methodologies: the descriptive approach to examine the theoretical concepts and practical realities of transformational leadership and human resource performance, and the analytical approach to process the field data. Data were collected from the study population, consisting of all bank employees (38 employees), using a questionnaire specifically designed for this purpose, and analyzed using SPSS software.The results indicated that the extent to which the requirements of transformational leadership were met was below the medium level from the perspective of the study population, with variations across its dimensions. The aspects related to inspiring enthusiasm, encouraging creativity, motivating individual initiatives, and fostering pride in organizational affiliation recorded the lowest levels of application. Furthermore, human resource performance was found to be below the required level, with low work enthusiasm, initiative, job satisfaction, and limited administrative support. Linear regression analysis showed a statistically significant positive effect of transformational leadership on human resource performance, supporting the main hypothesis of the study.Based on these findings, the study recommended the necessity of enhancing the motivational and inspirational practices of managerial leadership, improving human resource performance by increasing work enthusiasm and initiative, providing sufficient administrative support, designing specialized training programs for leaders to implement transformational leadership practices, regularly monitoring and evaluating performance, and promoting a culture of initiative and creativity among employees to ensure improved organizational performance.
Keywords: Transformational Leadership, Human Resource Performance